Avaliação de bactérias nitrificantes em filtros biológicos submersos aerados - Delgado, Tatiana Cardoso (2009)
This study investigates a new treatment system of wastewater by anaerobic and aerobic biological filters for nitrogen modification. The main objective of this study was evaluate, on a pilot scale, quantitatively and qualitatively the bacterian nitrifying community in a experimental sewage treatment system made by aerobics biological filters in series, in search of figure out the dynamic of nitrogen modification process. It was collected and laboratorial analysed microbiologically, regarding NMP of Nitrosomonas e Nitrobacter, and physical-chemically considering nitrogen sequence. We conclude that: the association in aerobic biological filters under nutrition controlled conditions and oxygen level allows the appearance of bacterian community responsible for the nitrogen modification; the method used, despite its limitations, provided the selection of autotrophic nitrifying microorganisms, allowing the identification of Nitrosomonas and Nitrobacter; the flow direction tested in the experimental unit did not affect the nitrifying bacterial community, certainly because they were kept drowned and did not occur flow speed that could breake the formed biomass; the nitrification process happened in aerated biological filters in all phases of the research, comproved by microbiological tests; in the third phase of the research the increase of the oxygen rate was significant for the nitrificant bacterian community in the aerate biological filters, allowing its growth, occurring relation between the efficiency of nitrification system and the quantity of organisms responsible for this process; the conduit used in aerated biological filters showed satisfactory performance support material to the nitrifying bacteria development